Bertahannya Eksistensi Islam Wetu Telu di Tengah Islam Waktu Lima - Sukardiman Sukardiman (Pascasarjana IAIN Metro, 2022)
Abstrac Religion is an inseparable part of humans, as well as various forms of religious movement models, even many new religious movements. One of the new religious movements that is interesting to study is the wetu telu which is located on the island of Lombok. Wetu telu is a community that combines ancestral traditions and values. - Islamic values ​​in it. Examples of forms of religious syncretism and ancestral traditions in the wetu telu community are buang au, neluq, mituq, nyiwaq, matang puluh, metang dase, nyatus, nyiu/nyeribuk, ngurisang, ngitanang, merosok, rowah wulan, sampet jum’at, malaman qunut, malam likuran, maleman fitrah, lebaran topat, lebaran pendek, selamatan bubur puteq dan bubur abang, and maulud. The wetu telu community can continue to exist until now with all its uniqueness due to several things, namely the legitimacy of Kyai Kagungan, building inclusive interactions with Islam Time Lima based on Ancient Mosque tourism, and of course social media as a basis for continuing to exist in the current era of very strong media. Key Word: Wetu Telu, Lombok Islam, Sinkretism